Special'nye uprazhnenijav legkoatleticheskom mnogobor'e - Dobrynskaya, N. (Science in Olympic Sport, 2019)
Track and field combined events are characterized by the extraordinary variety and complexity of the requirements for the athletes to have special technical, physical and mental fitness, which requires the use of various exercises in the training process. Objective. Substantiation of rational use of highly efficient special exercises in track and field combined events. Methods. Analysis and generalization of data of scientific and methodological literature, generalization of own experience of preparation, autoexperiment, methods of statistical analysis. Results. A wide range of special exercises that have a special focus in track and field combined events (hurdling, high jumping, shot put, long jumping, javelin throwing, running) are presented in detail - from the simplest, focused on general technique characteristics to the most complex contributing to improve the details of technical skill in interaction with the components of physical and psychological preparation. The use of such exercises with a focus on quality characteristics with a relatively small amount of training work is an essential factor not only in ensuring high athletic skills, but also in the prevention of fatigue, mental exhaustion, overtraining and traumatism. It is just this approach in the content of the training process that has allowed to achieve sports success, and, most importantly, to improve sportsmanship and stay in the elite sport for many years. It should be noted that before the first successes at the age of 16-18 years, a strong functional foundation was laid, which later allowed to pay attention at the technical component, only maintaining the previously achieved level of functional fitness. Conclusion. In case of creative approach, the exercises presented in the article can be applied in the sports practice of athletes specializing in track and field combined events.